Structure, electrical conductivity, and Raman spectra of (Cu1–xAgx)7GeS5I and (Cu1–xAgx)7GeSe5I mixed crystals. (March 2021) - Studenyak, I.P.; Pogodin, A.I.; Studenyak, V.I.; Filep, M.J.; Kokhan, O.P.; Kúš, P.; Azhniuk, Y.M.; Zahn, D.R.T.
Graphical abstract: Highlights: From XRD, (Cu1– x Ag x )7 GeSe5 I structure is described and compared to (Cu1– x Ag x )7 GeS5 I. Compositional behaviour of ionic and electronic conductivities is analysed. Raman spectra agree with the XRD data regarding their cubic structure. Abstract: The structure of (Cu1– x Ag x )7 GeSe5 I mixed crystals with Cu + ↔Ag + substitution is described and compared to (Cu1– x Ag x )7 GeS5 I employing the results of X-ray diffraction (XRD) and the atomic coordinates by Rietveld refinement. Based on the electrical measurements, the compositional behaviour of ionic and electronic conductivity as well as the ratio of ionic and electronic components of conductivity for (Cu1– x Ag x )7 GeS5 I and (Cu1- x Ag x )7 GeSe5 I is discussed. Raman spectra of (Cu1- x Ag x )7 GeSe5 I and (Cu1- x Ag x )7 GeSe5 I are consistent with the XRD data regarding their cubic structure. A one-mode compositional behaviour of the most prominent peak (corresponding to the vibrations of GeS4 or GeSe4 tetrahedra) under Cu→Ag cation substitution is observed, an unexpectedly strong shift of the peak frequency with x reveals its marked effect on the dynamics of GeS4 or GeSe4 tetrahedra. Compounds with high Ag content undergo photochemical surface transformations under laser irradiation during Raman measurements.